YOZUV KOʻNIKMASINI SHAKLLANTIRISH UCHUN MASHQLAR TIZIMI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In this article, we have revealed the formation and development of writing skills, which is one of the most pressing problems today, and the system of exercises as an example.
Keywords: Introduction to the topic, writing skills, alphabet, type of writing and speech activity, writing criteria.